The battle for the neuron’s wings - BLAGA, Raluca (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
The following study uses as its starting point the ancient battle between philosophy and theatre and takes as a road companions it’s two most famous protagonists: Plato and Aristotle. Taking a close look at their writings, I found not only an answer considering their battle for knowledge, for the encirclement of the spectator’s mind, but also the traces of one ‘predecessor’ of neuroscience – Aristotle. Informed by John Onians’s theories regarding neuroscience, art and history, and also adding neural plasticity as an ingredient, I’ve built my own personal (sup)position regarding catharsis, which I see as a two-fold experience/process - an emotional catharsis and a reasoning, reflexive catharsis.